Use of nitrogen from fertilizer and cover crops by upland rice in an Oxisol under no-tillage in the Cerrado - Silva, Edson Cabral da (2016)
The objective of this work was to evaluate the effects of cover crops on the yield of upland rice (Oryza sativa) grown under no-tillage system, in the presence and absence of N fertilizer, as well as to quantify, in the field, the use efficiency of N from urea and cover crops by upland rice, through the N-15 isotope dilution technique. The field experiment was carried out in the municipality of Selviria, in the state of Mato Grosso do Sul, Brazil, in an Oxisol (Rhodic Hapludox) in the Cerrado (Brazilian savanna) region. The experimental design was a randomized complete block with 15 treatments and four replicates, in a 5x3 factorial arrangement. The treatments were four cover crops (Crotalaria juncea, Cajanus cajan, Mucuna pruriens, and Pennisetum glaucum) + spontaneous vegetation (fallow in off-season), combined with three forms of N fertilization: control treatment, without N fertilizer application; 20 kg ha(-1) N at sowing; and 20 kg ha(-1) N at sowing plus 60 kg ha(-1) N as topdressing. Rice is not affected by N fertilizer application as topdressing, when legume cover crops are used. The use of legume cover crops provides higher grain yield and use of fertilizer-N by rice than that of millet or fallow. Legume cover crops promote an effect equivalent to that of the application of 60 kg ha(-1) N as urea on rice yield.